2015
DOI: 10.17356/ieejsp.v1i3.112
|View full text |Cite
|
Sign up to set email alerts
|

Changing movements, evolving parties: the party-oriented structure of the Hungarian radical right and alternative movement

Abstract: Two parties gained seats in the Hungarian parliament for the first time in the general elections of 2010. Both of these parties had a strong movement background, which seemed to be more obvious in the case of the radical right Jobbik, but the green LMP party also had strong ties to the Hungarian alternative movement. In this article I analyze the structural changes of the movements, which resulted in the dominance of the party-oriented structure. First, I look at the transformation of these movements from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Even twenty-five years after the transition, in 2014, three of the four parties in the Hungarian parliament had deep roots in the Kádár-era opposition movements. Dániel Mikecz showed that the trajectories of the farright movement and the ecological movement, both present in the 1980s, involved partially transforming into parliamentary parties by the early 2010s (D. Mikecz, 2015).…”
Section: Social Movements: the Hungarian Casementioning
confidence: 99%
“…Even twenty-five years after the transition, in 2014, three of the four parties in the Hungarian parliament had deep roots in the Kádár-era opposition movements. Dániel Mikecz showed that the trajectories of the farright movement and the ecological movement, both present in the 1980s, involved partially transforming into parliamentary parties by the early 2010s (D. Mikecz, 2015).…”
Section: Social Movements: the Hungarian Casementioning
confidence: 99%
“…the 'political opportunity structure' Tarrow 1994), 'frames' (Snow and Benford 1988), and the dynamic processes subtending them (McAdam et al 1996)to analyse far-right organisations (e.g. Diani 1996;Elgenius and Rydgren 2018;Froio and Ganesh 2018;Hutter and Borbáth 2018;Klandermans and Mayer 2005;Klein and Muis 2018;Mikecz 2015;Pytlas 2016;Rydgren 2005;Tipaldou and Uba 2018;Varga 2008). The growing corpus of interdisciplinary research testifies the value of understanding developments in the extra-parliamentary and institutional arenas as interdependent.…”
Section: Ballots and Barricades Enhanced 785mentioning
confidence: 99%
“…With 19.1 per cent of votes gained in the 2018 general elections, Jobbik currently qualifies as the biggest opposition force in the National Assembly and the second most voted party in Hungary. The social scientific literature has rarely analysed the Hungarian organisation from a social movement perspective (Mikecz ; Pirro and Róna ; Pirro and Castelli Gattinara ).…”
Section: Jobbik Between ‘Ballots and Barricades’mentioning
confidence: 99%
“…While this might be somewhat of a surprise for Hungarian politics, the discursive proximity of the then-far-right, populist political force and a green party with a strong component of social, distributive justice is more bewildering. In spite of the continuous shifts in the Hungarian opposition, LMP and Jobbik are both parties that rely heavily on their grassroots base (Mikecz 2015), although the support of the rural electorate is considerably smaller in the case of LMP. However, this is where LMP's endorsement of the 'neo-rurals', younger farmers and the newcomers to the Hungarian countryside, emerged as a theme in several interviews (12 and 13), and which can be impactful for the potential cooperation in agricultural matters.…”
Section: Competing Populisms?mentioning
confidence: 99%